Individual'naja ocenka bioenergeticeskich pokazatelej begunov na srednie distancii - Kryazhev, V. D.; Kryazhev, S. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Based on the Péronnet-Thibault model and the Vandewall equation describing the distance-time relationship, an applied computer program has been developed that allows to calculate bioenergetic indicators of medium-distance running (aerobic power and anaerobic performance, critical run speed and running speed on anaerobic exchange level) as a result of performance at distances from 400 to 3000 m. The results of the calculation of VO2max and Vcr for world record holders and Russia, as well as for students, runners of different qualifications are given. Discusses the further development of mathematical models of running, their shortcomings and the application for managing the training process of middle distance runners.